2013
DOI: 10.3892/ol.2013.1606
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation as an epigenetic biomarker in colorectal cancer

Abstract: Sporadic colorectal cancer (CRC) is a consequence of the accumulation of genetic and epigenetic alterations that result in the transformation of normal colonic epithelial cells to adenocarcinomas. Studies have indicated that a common event in the tumorigenesis of CRC is the association of global hypomethylation with discrete hypermethylation at the promoter regions of specific genes that are involved in cell cycle regulation, DNA repair, apoptosis, angiogenesis, adhesion and invasion. The present study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 20 publications
3
56
0
Order By: Relevance
“…APC hypermethylation has been already described in adenoma and CRC tissue and CRC plasma samples. 19,47,48 In accordance with findings of Judson et al, 48 hypermethylation in the active promoter of the APC gene in adenoma samples was detected in our study as well (Table 6). Similar alteration appeared in CRC samples, but in a different Log FC values are indicated only in cases of P < 0.05.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…APC hypermethylation has been already described in adenoma and CRC tissue and CRC plasma samples. 19,47,48 In accordance with findings of Judson et al, 48 hypermethylation in the active promoter of the APC gene in adenoma samples was detected in our study as well (Table 6). Similar alteration appeared in CRC samples, but in a different Log FC values are indicated only in cases of P < 0.05.…”
supporting
confidence: 92%
“…Correspondingly to the previous findings, 11,17,[19][20] we found that another known inhibitor of canonical WNT pathway, DKK2, was significantly hypermethylated in CRC vs. NAT and AD vs. NAT comparisons. However, our promoter estimation considering the sequence in the region between 2000 bp upstream and 1000 bp downstream from the transcription start site (if the positive DNA strand was the coding strand) identified 'active promoter' in at least one of the 9 analyzed cell lines, according to the ENCODE ChromHMM results.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…However, another study indicated that HNF1B may function as a tumor suppressor gene in chromophobe renal cell carcinogenesis through control of PKHD1 expression (15). It has been proven that HNF1B is downregulated in ovarian, gastric, pancreatic and colorectal cells (16,17), and its suppression influences cellular phenotypes associated with tumor-related properties in prostate cancer cells (18). The associations of HNF1B with cancer focus mainly on the single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…Ying et al (18) demonstrated that the transcriptional silencing of PCDH10 may be reversed by pharmacologic demethylation with 5-aza-2'-deoxycytidine or genetic demethylation with double knockout of DNA methyltransferase (DNMT)1 and DNMT3B in the colorectal cancer HCT116 cell line, suggesting a direct epigenetic mechanism (18). The aberrant methylation of the PCDH10 promoter was also observed in 43-85% of colorectal cancer tissues in several studies, indicating that PCDH10 methylation is a frequent event in colorectal carcinogenesis (11,35,39). In the present study, PCDH10 methylation was detected in colorectal cancer samples, but not in paired adjacent colorectal tissues, in accordance with the study by Yu et al (35), suggesting that the aberrant promoter methylation of PCDH10 is specific to colorectal cancer cells.…”
Section: Aberrant Promoter Methylation and Inactivation Of Pcdh10 In Crcmentioning
confidence: 99%